Menguji Konsep Hidden Divergence pada Indikator Momentum Relative Strength Index - T. Syifa Fadrizha Nanda (JRAK: Journal of Accounting Research and Computerized Accounting, 2024)
Due to the lack of empirical research exploring the application of the hidden divergence concept, this study aimed to evaluate the reliability of hidden divergence signals generated by momentum indicators to identify changes in the direction of price movements in the Indonesian Sharia Stock Index (ISSI). Time series data on daily movements of the Indonesian Sharia Stock Index (ISSI) from May 2011 to May 2023 are employed to observe the confirmation between price movements and the relative strength index (RSI) momentum indicator in order to identify hidden divergence signals. This study simulates a trading system using a technical analysis approach to see if hidden divergence signals could be relied on to forecast price movements. According to the findings of this study, price changes in a market can be predicted by studying the initial signs produced by the relative strength index (RSI), specifically when it forms a hidden divergence signal as an early warning in projecting future market movements.